Teaching climate change in the Anthropocene: An integrative approach. (June 2020) - Leichenko, Robin; O'Brien, Karen
Abstract: Why are we still educating college and university students through a Holocene lens? How can we expect young people to engage with the transformative challenges required to meet the targets of the Paris Agreement when climate change education is organized in a narrow and linear fashion? Climate change courses and teaching modules largely emphasize scientific literacy through a focus on physical processes, documentation of rising emissions, and empirical evidence of a changing climate. Classroom explorations of responses to climate change are often limited to "business-as-usual" policy options, new technologies, and behavioral interventions to reduce emissions or promote adaptation. Such approaches make it difficult for students to recognize the social dimensions of climate change and to identify openings and entry points for sustainability transformations. This Viewpoint contribution argues that it is time to rethink climate change curricula within higher education and adapt it to the Anthropocene. We present an integrative approach to climate change education that focuses on humans as active and reflexive agents of large-scale systems change, incorporates economic, political, cultural, psychological, and emotional dimensions of the issue, and fosters active engagement with transformations to sustainability.